Anti-apoptosis effect of amino acid modified gadofullerene via a mitochondria mediated pathway. Issue 22 (13th May 2019) - Yu, Tong; Zhen, Mingming; Li, Jie; Zhou, Yue; Ma, Haijun; Jia, Wang; Wang, Chunru
Abstract : A proposed molecular mechanism of the anti-apoptosis effect of GF-Ala through a mitochondria mediated pathway. Abstract : Metallofullerene Gd@C82 derivatives have been found to exhibit excellent performance in the treatment of chronic diseases and in tumor therapy due to their excellent anti-oxidation ability. Thus, there is a great need to clarify the specific protection mechanism of Gd@C82 derivatives against oxidative stress at the cellular and molecular level. Herein, we optimize the preparation of amino acid derivatives of Gd@C82 (GF-Ala) and investigated the potential mechanism of anti-oxidative stress induced by H2 O2 in L02 human hepatic cells. GF-Ala with excellent biocompatibility and high production yield was obtained by adjusting the size of solid Gd@C82 as a starting material. Pretreatment with GF-Ala significantly improved the cell viability of oxidatively damaged cells. Furthermore, we found that GF-Ala prominently reduced intracellular reactive oxygen species (ROS) production, stabilized mitochondrial membrane potential (MMP) and inhibited cell apoptosis. Moreover, GF-Ala up-regulated the expression of Bcl-2 and down-regulated the expression of Bax, which further prevented the activation of pro-caspase 3 and PARP. Thus, we showed that GF-Ala protected the cells from oxidative stress by blocking the mitochondria-mediated apoptosis pathway.